Efficiency of Ferritin as an MRI Reporter Gene in NPC Cells Is Enhanced by Iron Supplementation. (20th March 2012) - Feng, Yupeng; Liu, Qicai; Zhu, Junfeng; Xie, Fukang; Li, Li
Abstract : Background . An emerging MRI reporter, ferritin heavy chain (FTH1), is recently applied to enhance the contrast and increase the sensitivity of MRI in the monitoring of solid tumors. However, FTH1-overexpression-related cytotoxicity is required to be explored. Methods . By using the Tet-Off system, FTH1 overexpression was semi-quantitativiely and dynamicly regulated by doxycycline in a NPC cell line. Effects of FTH1 overexpression on the proliferation, cytotoxicity, apoptosis and migration of NPC cells were investigated in vitro, and MR relaxation rate was measured in vitro and in vivo . Results . In vitro and in vivo overexpression of FTH1 significantly increased the transverse relaxivity (R 2 ), which could be enhanced by iron supplementation. In vitro, overexpression of FTH1 reduced cell growth and migration, which were not reduced by iron supplementation. Furthermore, cells were subcutaneously inoculated into the nude mice. Results showed FTH1 overexpression decreased tumor growth in the absence of iron supplementation but not in the presence of iron supplementation. Conclusion . To maximizeR 2 and minimize the potential adverse effects, supplementation of iron at appropriate dose is recommended during the application of FTH1 as a reporter gene in the monitoring of NPC by MRI.